Reading Malir Cantonment in Karachi, Pakistan: some notes on residential barracks and spatial dynamics - Nasir, Muhammad Ali (Contemporary South Asia, 2014)
This article considers the way in which the ‘microphysics of power’ works on space and impacts on spatial politics. I focus on the transformation of one cantonment from a military garrison into a ‘residential barrack’: the Malir Cantonment in Karachi, Pakistan. The paper begins by tracing the history of cantonments, before locating the Malir Cantonment in the changing political, economic, and demographic dynamics of Karachi. Through this, the article focuses on the mechanisms through which Malir Cantonment functions as a residential barrack.
Gesehen am 18.01.2021